2011
DOI: 10.4085/1062-6050-46.2.206
|View full text |Cite
|
Sign up to set email alerts
|

National Athletic Trainers' Association Position Statement: Prevention of Pediatric Overuse Injuries

Abstract: Objective: To provide certified athletic trainers, physicians, and other health care professionals with recommendations on best practices for the prevention of overuse sports injuries in pediatric athletes (aged 6-18 years).Background: Participation in sports by the pediatric population has grown tremendously over the years. Although the health benefits of participation in competitive and recreational athletic events are numerous, one adverse consequence is sport-related injury. Overuse or repetitive trauma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(106 citation statements)
references
References 76 publications
3
96
0
7
Order By: Relevance
“…Recent data examining acute resistance training-related injuries in youth and adults reveal that approximately 77.2% of all injuries are accidental103 and that most injuries are potentially avoidable with appropriate supervision, sensible training progression based on technical competency and a safe training environment 29. With respect to overuse injuries, literature indicates that appropriately prescribed and well-supervised training programmes will reduce the likelihood of overuse injuries occurring in youth populations120122 and that resistance training focused on addressing the risk factors associated with youth-sport injuries (eg, low-fitness level, muscle imbalances and errors in training) has the potential to reduce overuse injuries by approximately 50% in children and adolescents 26 123. For example, training protocols incorporated into preseason and in-season conditioning programmes reduced overuse injury risks, and decreased anterior cruciate ligament (ACL) injuries in adolescent athletes 124 – 128…”
Section: Injury Prevention Benefits Of Resistance Training For Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data examining acute resistance training-related injuries in youth and adults reveal that approximately 77.2% of all injuries are accidental103 and that most injuries are potentially avoidable with appropriate supervision, sensible training progression based on technical competency and a safe training environment 29. With respect to overuse injuries, literature indicates that appropriately prescribed and well-supervised training programmes will reduce the likelihood of overuse injuries occurring in youth populations120122 and that resistance training focused on addressing the risk factors associated with youth-sport injuries (eg, low-fitness level, muscle imbalances and errors in training) has the potential to reduce overuse injuries by approximately 50% in children and adolescents 26 123. For example, training protocols incorporated into preseason and in-season conditioning programmes reduced overuse injury risks, and decreased anterior cruciate ligament (ACL) injuries in adolescent athletes 124 – 128…”
Section: Injury Prevention Benefits Of Resistance Training For Youthmentioning
confidence: 99%
“…From a health perspective, evidence indicates that resistance training can make positive alterations in overall body composition,18 reduce body fat,19 20 improve insulin-sensitivity in adolescents who are overweight21 and enhance cardiac function in children who are obese 22. Importantly, it has also been demonstrated that regular participation in an appropriately designed exercise programme inclusive of resistance training, can enhance bone-mineral density and improve skeletal health23 24 and likely reduce sports-related injury risk in young athletes 25 26. This would appear to be an important consideration given that approximately 3.5 million sports-related injuries in youth require a medical visit each year in the USA 27.…”
Section: Introductionmentioning
confidence: 99%
“…The development of movement compe-tency is characterized by an early bias towards enhancing fundamental movement skills with a transition over time towards a greater emphasis on sport-specific skills. Early exposure to resistance training is supported by research, which shows that muscular strength development from resistance training can enhance physical performance (29), improve markers of health and well-being (such as insulinsensitivity (47) and levels of adiposity (8)) in active and inactive youth, and reduce the risk of sports-related injury ( 17,35,38,55). Additionally, movement skill competency is associated with physical activity engagement and improved measures of health and well-being in both normal and over-weight/obese youth (11,28,32).…”
Section: Athletic Development Modelsmentioning
confidence: 99%
“…Eleven core counselling recommendations were generally Strength of Recommendation Taxonomy Level B and C recommendations from the AMSSM position statement,12 NATA11 position statement and a 2015 study on relationship between sports specialisation, training patterns and injury risk in young athletes 19. For ethical reasons, at the conclusion of the study, both study groups received a counselling ‘checklist’ outlining all the study recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Several professional medical organisations, including the American Academy of Pediatrics,15 the American Medical Society for Sports Medicine (AMSSM),12 the National Athletic Trainer’s Association (NATA)11 and the American Orthopaedic Society for Sports Medicine,16 provide recommendations for preventing overuse injuries in young athletes; however, athletes’ compliance with these recommendations and their subsequent effectiveness for preventing injuries have not been thoroughly evaluated. Notably, while some recommendations may be valuable, barriers to compliance may hamper a young athlete’s adherence to the available recommendations.…”
Section: Introductionmentioning
confidence: 99%